Eringiacetal A, 5, 6‐seco‐(5S, 6R, 7R, 9S)‐5, 6:5, 7:6, 9‐Triepoxyergosta‐8(14), 22‐diene‐3β, 7β‐diol, an Unusual Ergostane Sterol from the Fruiting Bodies of Pleurotus eryngii. Issue 21 (10th June 2015) - Kikuchi, Takashi; Masumoto, Yuki; In, Yasuko; Tomoo, Koji; Yamada, Takeshi; Tanaka, Reiko
Abstract: A new rearranged ergostane‐type steroid, named eringiacetal A (1 ), together with known compound2, were isolated from the fruiting bodies of Pleurotus eryngii (Pleurotaceae). Its structure was fully elucidated by NMR spectroscopy and X‐ray crystallography. Eringiacetal A (1 ) features an unprecedented 5, 6‐ seco ‐(5 S, 6 R, 7 R, 9 S )‐5, 6:5, 7:6, 9‐triepoxyergosta‐8(14), 22‐diene‐3β, 7β‐diol. This is the first report of a 5, 6‐ seco ‐ergostane‐type steroid. A plausible biogenetic pathway of1 from2 is also described. Furthermore, isolated compounds were evaluated for inhibitory effects on nitric oxide (NO) production induced by lipopolysaccharide in macrophages. Compound1 exhibited inhibitory activity on NO production (IC50 = 19.9 μM ) accompanied by modest cytotoxicity (IC50 = 25.6 μM ). Compound2 did not have inhibitory effects on NO production or cytotoxicity (IC50 > 100 μM each). Abstract : A new rearranged ergostane‐type steroid, named eringiacetal A, was isolated from the fruiting bodies of Pleurotus eryngii (Pleurotaceae). Its structure was established by spectroscopic analyses and X‐ray crystallography. Eringiacetal A features an unprecedented 5, 6‐ seco ‐(5 S, 6 R, 7 R, 9 S )‐5, 6:5, 7:6, 9‐triepoxyergosta‐8(14), 22‐diene‐3β, 7β‐diol.